2015
DOI: 10.1177/147776061503100401
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Nature of Vulcanisation Fumes in the Rubber Industry – a Technical Review

Abstract: Industrial hose Water hose, high pressure hose, welding hose, hydraulic hose, spiral hose, Offshore hose, oil hose, chemical hoses Automotive products Hoses & gaskets, anti-vibration mounts, timing belts, window and door seals, transmission and engine components, wiper blades General mouldings/ sheeting Seals & gaskets, floor and roller coverings, sheeting, protection linings, micro-cellular products, rubberized fabric, wire and cable jackets, pump impellors, rail mounts, bridge bearings Medical/pharma product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Fourth, this review included rubber manufacturing emissions studies from over a span of 42 years. During this period, substantial changes in rubber manufacturing work practices have occurred, which potentially affected the comparability or contemporary relevance of some of the results and conclusions. Finally, our review was restricted to published studies written in the English language, which might have underestimated the occurrence of NMRD among rubber workers and the systematic review results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, this review included rubber manufacturing emissions studies from over a span of 42 years. During this period, substantial changes in rubber manufacturing work practices have occurred, which potentially affected the comparability or contemporary relevance of some of the results and conclusions. Finally, our review was restricted to published studies written in the English language, which might have underestimated the occurrence of NMRD among rubber workers and the systematic review results.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 500 ingredients are combined to produce various types of rubber . During rubber manufacturing, workers are potentially exposed to feedstock materials and reaction products released in the forms of gases, vapors, dusts, mists, and ultrafine particles, collectively referred as rubber manufacturing emissions …”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, more VOCs and harmful factors are generated in the synthetic rubber manufacturing industry (SBR, NBR, EPDM rubber) than in the tire manufacturing industry. Accordingly, this suggests that more research is needed in the rubber-related manufacturing industry than in the tire manufacturing industry [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this reduction is mainly due to technological improvement ways, modernisation of ventilation and extraction equipment and changes in working practices. As an example, the evaluation of the environmental impact of the gaseous emissions from the rubber manufacturing by the Swedish Environmental Protection Agency in 1991 revealed that the cessation of chemicals use or the replacement of chemicals that are harmful to human health and environment by safer ones are part of a global approach which aims for improvements in the production process (Forrest, 2015). However it is important that besides the efforts towards safer workplaces, technologies are also developed and implemented to control the emissions to the environment in particular stack exhaust emissions (Rosen and Kishawy, 2012), where it is common to find mixtures of biodegradable (such as alcohols) and more recalcitrant (mixtures of alkanes) Volatile Organic Compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%